Parent-Child Interaction Therapy in a Case of Global Developmental Delay and Leukoencephalopathy - Shafi, Reem M.A.; Vande Voort, Jennifer L.; Croarkin, Paul E.; Romanowicz, Magdalena (Frontiers in Psychiatry, 2018)
Parent-child interaction therapy (PCIT) is an evidence-based, behavioral dyadic treatment for caregivers and their children aged 2-7 years old with emotional and behavioral disorders. Here we present a treatment course of a 3-year-old girl with leukoencephalopathy, dysgenesis of the brainstem, and associated global developmental delay. At the beginning of PCIT she had the developmental level of an 18month old with language skills of a 12-18month old; both her vocabulary and verbal expression were very limited. She was referred to Psychiatry with concerns regarding disruptive behaviors including severe self-injury. PCIT was started with a focus on PRIDE skills (Praise, Reflection, Imitation, Behavioral description and Enjoyment); particularly behavioral description and reflection with simple developmentally appropriate labelled praise. Modifications to treatment included using non-verbal actions (e.g. ‘high fives’ as praises), sign language and using only one-step basic commands, which greatly improved compliance. In a matter of weeks, the patient demonstrated remarkable improvement in her disruptive behavior as evidenced by parent/daycare report and clinical observation. Surprisingly her vocabulary more than doubled and her ability of self-expression also increased; she was able to point to things and ask for them. This clinical experience suggests that PCIT principles are effective treatment interventions for other clinical presentations outside of the usual inclusion criteria. Implementation of targeted PCIT interventions greatly benefited the development of language skills and communication in a young child with global developmental delay.